2015
DOI: 10.1080/10408398.2014.1001019
|View full text |Cite
|
Sign up to set email alerts
|

Tea and bone health: Findings from human studies, potential mechanisms, and identification of knowledge gaps

Abstract: The population of the developed world is aging. With this aging population, strategies for prevention rather than treatment of chronic disease, such as osteoporosis, are essential for preserving quality of life and reducing health care costs. Tea is the second most consumed beverage in the world and is a rich source of flavonoids that may benefit bone health. There is strong evidence from human studies that habitual tea consumption is positively associated with higher BMD at multiple skeletal sites, while the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
32
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 51 publications
(32 citation statements)
references
References 122 publications
0
32
0
Order By: Relevance
“…Two human epidemiological studies found positive associations between total dietary flavonoid intake and bone mineral density (BMD) in women (Welch & Hardcastle, ) and cross‐sectional studies also report positive associations between habitual tea consumption and BMD (Nash & Ward, ), although experimental evidence is limited. In rodent models quercetin 1 was shown to improve bone mineral density (Kawabata, Mukai, & Ishisaka, ), hesperetin‐7‐ O ‐rutinoside inhibited bone resorption (Li & Schluesener, ) and, although limited mechanistic data are presently available, Nash and Ward () proposed modulation of osteoblastic and osteoclastic activity as a possible mechanism of action.…”
Section: Bioactivitymentioning
confidence: 99%
“…Two human epidemiological studies found positive associations between total dietary flavonoid intake and bone mineral density (BMD) in women (Welch & Hardcastle, ) and cross‐sectional studies also report positive associations between habitual tea consumption and BMD (Nash & Ward, ), although experimental evidence is limited. In rodent models quercetin 1 was shown to improve bone mineral density (Kawabata, Mukai, & Ishisaka, ), hesperetin‐7‐ O ‐rutinoside inhibited bone resorption (Li & Schluesener, ) and, although limited mechanistic data are presently available, Nash and Ward () proposed modulation of osteoblastic and osteoclastic activity as a possible mechanism of action.…”
Section: Bioactivitymentioning
confidence: 99%
“…F indings from prospective and cross-sectional studies, mostly in postmenopausal women, suggest a positive association between habitual tea drinking and higher bone mineral density (BMD). [1][2][3][4][5][6][7] In a prospective study of older women (>75 years old) who were at risk of fracture, habitual consumption of three or more cups of black tea (BT) per day was associated with a 30% reduction in fracture risk. 2 There is a paucity of data in men with two studies showing no association and another study showing a positive association between higher tea intake and higher BMD.…”
Section: Introductionmentioning
confidence: 99%
“…Beyond calcium and vitamin D, a wide range of foods, nutrients, and food components have been studied for their bone building or supportive actions [6][7][8][9][10]. One potential strategy of promoting and supporting bone health is through the consumption of tea [11]. Consumption of black and green tea is associated with reduced incidence of cancer as well as cardiovascular disease, often attributed to the presence of polyphenols found in tea [12,13].…”
Section: Introductionmentioning
confidence: 99%